Effects of Groundwater Depth and Salt Content on Vegetation in Dry Lake Basins: A Case Study of Chahan Lake, Northern China - Peng Chen; Rong Ma; Jiansheng Shi; Letian Si (Geofluids)
Under the dual influences of global climate change and human activities, inland lakes in arid areas are shrinking and drying up, and a large area of bare lake bed has become the source of the release of chemical dust. The aim of this study is to study the control of groundwater on the distribution and development of natural vegetation and the effects of the groundwater conditions on soil salinization. In this study, a typical modern dry lake in northern China, Chahan Lake, was taken as the study area. Through field investigations, field sampling and analysis, and statistical analysis, the influence of groundwater on the ecosystem of this dry lake was studied. The results revealed that the vegetation communities in the lakeside zone were Kalidium foliatum, Nitraria tangutorum, Suaeda glauca, Leymus chinensis, Chloris virgata, and Carex duriuscula communities from the dry lake bed outwards. The groundwater table suitable for vegetation growth in Chahan Lake is 2.0–3.0 m deep. The groundwater table suitable for the growth of Kalidium foliatum vegetation is 1.5–2.5 m deep. The groundwater table suitable for the growth of Leymus chinensis vegetation is 3.0–4.0 m deep. In Chahan Lake, the critical groundwater depth and total dissolved solids (TDS) for moderate salinization, severe salinization, and saline soil occurrence are 4.0 m and 2.0 g/L, 3.0 m and 3.0 g/L, and 1.5 m and 4.0 g/L, respectively. Regarding the prevention and control of salt-dust storms, the ecological threshold of the groundwater, which can effectively increase the vegetation coverage and prevent soil salinization, is groundwater depths of 2.0–4.0 m and TDS values of <2 g/L.